The value of health - Brink Henriëtte; Groot Wim (BMC, 2008)
Abstract Background A major problem in cost-effectiveness studies is where to draw the line between interventions which are cost-effective and those who are not. Lacking a notion about the value of a QALY, all ultimate values to the cost-effectiveness ratio are essentially arbitrary. Methods This paper presents a simple empirical model to estimate the compensating income variation of diseases and health problems. The model is estimated using data for the Netherlands. Results The compensating income variation is between €20,000 and €90,000. This is higher than most of the ultimate values used by policy-makers to decide whether an intervention is cost-effective. Our figures are roughly similar to those found in studies about the value of a statistical life year. Conclusion Estimates on the compensating income variation of diseases and health problems may provide useful information on the maximum acceptable cost-effectiveness ratio of medical interventions than those currently used by policy makers.